Analyzing the Competitiveness of Balmazujvaros on the Basis of a SWOT-Analysis, Emphasizing Tourism - Tarné Klutsik, Andrea (Acta Agraria Debreceniensis, 2004)
My study examined the competitiveness of Balmazujvaros, in regard to tourism. The town is situated in the Northern Great Plain region, in Hajdu-Bihar county, 22 km from Debrecen, together with Egyek, Hortobagy and Tiszacsege joined the statistical subregion of Balmazujvaros. Comparing with the neighbouring settlements, it has similar geographical features and posesses thermal water that was determined to be medicinal, which is a feature of the region. Balmazujvaros as a typical country town as it has a dominant agricultural character. It gained town status in 1989. Part of the town is situated in the National Park of Hortobagy. The first part of my study is to determine the number of rival settlements from the viewpoint of tourism. I will analyze the results of a questionnaire given to tourists in Balmazujvaros between June 15 August 31 2003, and introduce the primary results. The SWOT analysis will show the primary and secondary information and the examination of the results. If we take into account the strengths, weaknesses, opportunities and threats of this town, we can make the following conclusion: tourism is an opportunity with a well-developed infrastructure, a third sector, subsidies and improved local interest. A sound and well-defined marketing strategy is essential for Balmazujvaros, in order to overwhelm its strong rivals